'Perspectives bâtardes': Stereoscopy, Cézanne, and the Metapictorial Logic of Spatial Construction. Issue 3 (3rd July 2017) - Bantjes, Rod
Abstract : Stereoscopy initiated a dimensional shift that freed representation from the laws of geometric optics and longstanding conventions of linear perspective, creating aesthetic possibilities that were first explored by now obscure stereo-photographers. The late nineteenth-century 'rupture in the pictorial order' that Hubert Damisch attributes to Paul Cézanne has a genealogy that includes stereoscopy, the debates about binocular space perception that it occasioned, as well as innovative photographic work for the stereoscope. Through reading Hippolyte Taine, Cézanne was aware of the Berkelean idea that binocular space is not seen, but rather assembled from visual and tactile sensation sampled across time. The problem that this understanding posed for representation led many to insist that binocular space could only be invoked through synthetic apparatuses like the stereoscope; others argued for new conventions of planar representation, or 'binocular painting'. The visual evidence from Cézanne's work suggests that he paid attention to prescriptions for binocular painting and also to the new pictorial language developed by stereo photographers. Stereo photographers in the 1850s and 1860s, by abandoning perspectival conventions and proposing a constructivist conception of space, helped to transform Western visual culture in hitherto unappreciated ways.